Bean sprout production technique in Ipoh [Peninsular Malaysia] - Lee, S.Y. (MARDI, Serdang, Selangor (Malaysia). Food Technology Div.) (2013)
Bean sprout production is simple and cheap. It does not need costly equipment, however, the return is outstanding. This article discusses the production steps which are commonly practised by bean sprout producers in Ipoh.